Magnetic energy conversion and runaway regeneration during fast deconfinement of vertically unstable disruption generated runaway beams - J.R. Martín-Solís; J.A. Mier; F.J. Artola; A. Loarte (Nuclear Fusion)
The fast deconfinement of a vertically unstable runaway beam is investigated using a 0-D model which includes self-consistently the vertical plasma motion and the generation of runaway electrons Kiramov and Breizman (2017 Physics of Plasmas 24 100702). It is found that due to the decay of the runaway current during deconfinement, the plasma is vertically accelerated, leading to a substantial enhancement of the electric field when it touches the wall, which can result in a large runaway avalanche, regeneration of the runaway current and noticeable energy deposition on the runaway beam. The dependence of the conversion of magnetic into runaway kinetic energy on the characteristic deconfinement time of the runaway electrons, the resistive time of the residual ohmic plasma during the disruption, and the initial current and position of the runaway beam is also investigated. Negligible conversion of magnetic into runaway kinetic energy and runaway regeneration are found for characteristic deconfinement times lower than 0.5 ms and low temperatures (a few eVs) of the residual ohmic plasma. Moreover, estimates of the power fluxes on the plasma facing components suggest that, unless the runaway current at deconfinement is small enough ( ${\lt}1\ MA$ ), shorter deconfinement times would be required to increase the runaway wetted area to levels enough to avoid melting of the first wall materials (Be or W).